In-Silico Screening Compounds of Brassica rapa ssp. chinensis as Potential Inhibitor of Neutral Amino Acid Transporter B0AT1 as an Alternative Phenylketonuria Treatment - Nathania, Nina Regina; Mantow, Jellyta Pricilla; Criswahyudianti, Elsa Rahmania; Atamimi, Fachrur Rozi; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
Phenylketonuria (PKU) is known as a severe autosomal recessive disease caused by mutations in the expression enzyme, namely the PAH (Phenylalanine Hydroxylase) enzyme that causes the build-up of phenylalanine in the body. Untreated PKU affected brain damage and developmental problems. One of the strategies to reduce phenylalanine in the body is inhibiting B0AT1 activity using carotenoid and terpenoids compounds from Bok choy (Brassica rapa ssp.chinensis). In this study, we evaluated the nine carotenoid and terpenoid compounds from Bok choy as B0AT1 inhibitors. Nine Bok choy compounds, including alpha-carotene, beta-carotene, dimethylallyl pyrophosphate, isopentenyl pyrophosphate, lutein, neoxanthin, violaxanthin, geranylgeranyl diphosphate, and zeaxanthin were downloaded from PubChem database, while the 3D structure of B0AT1 was retrieved from Protein Data Bank RCSB. The compounds and B0AT1 were prepared by PyRx 0.8 version and Discovery Studio ver 21.1.1, then docked with Hex 8.0.0 and analyzed using Discovery Studio ver 21.1.1. This screening implies that three terpenoid compounds dimethylallyl pyrophosphate, isopentenyl pyrophosphate, and geranylgeranyl diphosphate interacts in C domain of B0AT1 while six carotenoid compounds, alpha carotene, beta-carotene, lutein, neoxanthin, violaxanthin, and zeaxanthin interacts in A domain and have possibility to inhibit B0AT1, because it interact with same A domain and have a stronger binding energy than phenylalanine. Alpha carotene has a same residue with phenylalanine, Phe144, making it potentially greater than other compound as inhibitors. Brassica rapa ssp. chinensis is indeed good for consumption by people with phenylketonuria, but it is also necessary to do a further compound screening in other low-phenylalanine diet foods to know which one is better as alternative phenylketonuria treatment.